FINDS: fraud digital forensic tool / Rohana Othman … [et al.] - Othman, Rohana; Mohamed, Intan Salwani; Abdul Malek, Mohamad Affendi; Abdul Aris, Nooraslinda; Mohd Arif, Siti Maznah (Research Innovation Business Unit, 2014)
THE PRODUCT FINDS (Fraud Investigation, Detection and Monitoring Systems) is a Digital Forensic tool for fraud investigation, detection, and observation. Reports and researches have documented huge losses resulting from fraud, such as non-financial damage to reputation that may have long term negative repercussions. The situation is further exacerbated by a lack of manpower trained in fraud detection and investigation especially in identifying red flags. To facilitate fraud detection and investigation, an effective fraud detection computerized system is critically warranted. Thus, FINDS is seen as one of the important tools in digital forensic investigation activity. FINDS is equipped with various functions that will facilitate the monitoring of illegal incident. It also acts as a mechanism to assist in fraud investigations as fraud is seen to be a despicable act that has potentially devastating and long term negative impacts on organizations. FINDS will help to improve the current dire situation so as to enhance and improve damage control efforts. Additionally, it will help to overcome the current problem of inadequate monitoring of fraud red flags, notably because red flags are effective indicators of what future actions need to be taken. The system is developed using Java programming language and will be the first application of its kind (originality) as its represents a pioneering initiative. The advent of electronic commerce has led to the growth in fraudulent practices. This is evident by the increasing number of several high profile frauds reported. Some of the shortcomings that exist include shortage of knowledge concerning the characteristics of corporate fraud, auditors are lacking the necessary experience in detecting fraud and financial managers and accountants are deliberately trying to deceive the auditors. These shortcomings suggested that normal audit procedures to detect fraud have now become inadequate. Therefore, a need for additional analytical procedures for effective detection of false financial statements is critically needed. The key objective of FINDS is to detect, identify, and monitor fraud risks and fraud red flags. It is a user friendly system and able to entertain any level of user and functions are easily accessible by a single click. Besides, it is able to analyse a large number of transactions, identify trends, spot documents that need further review requiring more cost-effective and more comprehensive approach than just depending on hard-copy document review. This can be integrated with other software namely Ms Word, Ms Excel and Ms PowerPoint. It fulfils the National Strategic Agenda (NKEA) as set out by the Institute Integrity Malaysia (IIM) to eliminate corruption. The novelty of FINDS lies in its high versatility, utility and viability for commercialization as a tool to detect fraud and assess potential risks using forensic investigations. FINDS is a unique application to enable the conducting of effective digital forensic investigations into potential fraud risks and evaluate past fraud cases. FINDS isolates anomalies that relates to red flags to trigger fraud detection and investigation. FINDS is original software that holds the potential for commercialization and customization to suit all spectrum of fraud investigation in the public and private sectors. FINDS is a collaborative product of UiTM and Jabatan Akauntan Negara Malaysia.